Biomanufacturing for clinically advanced cell therapies. (June 2018) - Aijaz, Ayesha; Li, Matthew; Smith, David; Khong, Danika; LeBlon, Courtney; Fenton, Owen; Olabisi, Ronke; Libutti, Steven; Tischfield, Jay; Maus, Marcela; Deans, Robert; Barcia, Rita; et al.
Abstract The achievements of cell-based therapeutics have galvanized efforts to bring cell therapies to the market. To address the demands of the clinical and eventual commercial-scale production of cells, and with the increasing generation of large clinical datasets from chimeric antigen receptor T-cell immunotherapy, from transplants of engineered haematopoietic stem cells and from other promising cell therapies, an emphasis on biomanufacturing requirements becomes necessary. Robust infrastructure should address current limitations in cell harvesting, expansion, manipulation, purification, preservation and formulation, ultimately leading to successful therapy administration to patients at an acceptable cost. In this Review, we highlight case examples of cutting-edge bioprocessing technologies that improve biomanufacturing efficiency for cell therapies approaching clinical use. This Review discusses the manufacturing of cell products for clinically advanced cell therapies, and highlights potential manufacturing bottlenecks and solutions towards the cost-effective commercialization of the therapies.